The inclusive 15-minute city: Walkability analysis with sidewalk networks. (March 2023) - Rhoads, Daniel; Solé-Ribalta, Albert; Borge-Holthoefer, Javier
Abstract: In recent years, the design (and re-design) of cities to encourage walkability has taken on new urgency as part of a wider campaign for sustainable urban development. Complementary to other approaches like infrastructure improvements, increases in residential density, or traffic calming measures, here, we show how planning for walkability can be augmented by the adaptation of tools and approaches from the study of urban networks, by privileging the pedestrian perspective of short-distance access over the car (and rapid transit) perspective of flow and efficiency. Using a recently developed sidewalk network model that moves towards a more realistic representation of the pedestrian environment, we propose a framework for assessing multi-factor walkability using percolation theory and insights into pedestrian behavior. We apply our framework to the city of Barcelona, and show how it can be used to optimize service location and access for vulnerable populations (the elderly and young). Highlights: We develop a flexible framework to test the robustness of city sidewalk networks to residents' diverse mobility constraints, and apply it to Barcelona, Spain. We employ a sidewalk network model that captures the physical features of the walking infrastructure at city-wide and egohood levels. Even a pedestrian-friendly city like Barcelona does not hold up to the "15-minute city" when moderate physical constraints are taken into account. We identified a significant decline of access in key social and health services. Different approaches to improve access are discussed, i.e., establishing new services or facilitating access to existing ones.